Komparasi Perbedaan Persepsi Antara Penyusun dan Pengguna Laporan Keuangan dalam Rangka Perubahan Sistem Akuntansi Pemerintah Berbasis Akrual di Kota Sungai Penuh - Herlina, Vivi (Ebisma (Economics, Business, Management, & Accounting Journal), 2024)
This study aims to analyze the comparative Differences in Perception Between Compilers and Users of Financial Reports in the Region in the context of Changing the Accrual-Based Government Accounting System in Kota Sungai Penuh. This study uses a qualitative approach by conducting an interview process with informants to conduct the data analysis and triangulation process. The results of this study explain that there are differences in the perceptions of Compilers and Users regarding the implementation of Accrual-Based Accounting, compilers understand more in terms of compliance with the regulations. The implication of this study is that for the successful implementation of an accrual-based system, competent human resources are needed.